A comparative study of vacuum tumbling and immersion marination on quality, microstructure, and protein changes of Xueshan chicken - Ge, Qingfeng; Guo, Shuyang; Chen, Sheng; Wu, Yuehao; Jia, Zhaoyang; Kang, Zhuangli; Xiong, Guoyuan; Yu, Hai; Wu, Mangang; Liu, Rui (Frontiers in Nutrition, 2022)
Marination is a common technology in meat processing with advantages of enhancing tenderness, water retention, and overall quality. This study was conducted to investigate the effect of vacuum tumbling and immersion marination on meat quality, microstructure, water mobility, protein changes, and denaturation of Xueshan chicken. Results showed that vacuum tumbling significantly increased the marinating rate of chicken, tenderness, meat texture, and water retention. Meanwhile, vacuum tumbling decreased total sulfhydryl content alongside an increased protein surface hydrophobicity and free sulfhydryl content, indicating that vacuum tumbling elevated the degree of protein denaturation. Further, the peak area corresponding to the relaxation time T22 after vacuum tumbling was significantly higher than that of immersion marination, suggesting that the stability of the immobilized water of chicken was reduced by vacuum tumbling. Compared to immersion marination, vacuum tumbling improved myofibril fragmentation index (MFI) presenting fewer myofibrillar protein bands in sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) gel and more damaged muscular cells. Overall, vacuum tumbling could improve the marination absorptivity, protein degradation, and denaturation, resulting in changes in myofibril structure and meat quality of Xueshan chicken.